Effects of Arbuscular Mycorrhizal Fungi on Nutrient Uptake by Pericopsis mooniana in Media Post Gold Mining Land - Faisal Danu Tuheteru; Husna Husna; Nuranisa Nuranisa; Basrudin Basrudin; Asrianti Arif; Albasri Albasri; Ikraeni Safitri; Sedek Karepesina; Wiwin Rahmawati Nurdin (Asosiasi Mikoriza Indonesia, 2022)
This study aims to determine the levels and nutrient uptake of kayu kuku (Pericopsis mooniana Thwaites) mycorrhizal plants aged four months in post-gold mining field scale. Sampling was carried out in the post-Bombana gold mining area. Leaf drying and weighing wass carried out at the Laboratory of the Faculty of Forestry and Environmental Sciences, Halu Oleo University and measurement of nutrient content and uptake at the SEAMEO BIOTROP Soil and Plants Laboratory Bogor, this study started from May to Jully 2021. This research method used a Randomized Block Design (RBD) with 4 treatments, namely control (A), G. coronatum (B), G. claroideum (C) and mixed AMF (B+C). This study was divided into 3 groups where each group contained 1 plant so that the total plants used are 12 kayu kuku plants. The results showed that AMF G. coronatum significantly increased N, P and Mn nutrient levels. Mixed AMF (G. coronatum + G. claroideum) was effective in increasing nutrient uptake of N, P, Mn and Fe. AMF was effective in increasing the levels and nutrient uptake of the four month old P. mooniana on post-Gold Mining